Menanamkan Nilai-Nilai Pada Anak Melalui Keteladanan Orangtua - Vinsensius Bawa Toron; Andarweni Astuti (Jurnal Bimbingan dan Konseling Indonesia, 2022)
The three pillars of education namely family, school and community are the foundation for building today's educational civilization. The purpose of this research is to realize the role of parents and teachers as companions instilling values ​​to advance the dignity and nobility of the nation. The method used by researchers is a qualitative approach studying the literature and also using interviews, as supporting data. The findings, departing from some of the theories put forward in the introductory section, the researcher analyzed in several social media, newspapers, magazines and interviews found that relevant and creative methods in accompanying children to instill values ​​must match the reality they experience every day Together with parents in the family, teachers at school and friends in the community, it really helps students find their identity. Accompanying while instilling value, not only an expression but an action. Therefore the behavior of students needs to be analyzed, studied further and needs to be re-evaluated. From the results of the interviews, of these three pillars, the education of children in the family is under the responsibility of the parents. Meanwhile, education in schools is seen as a means of further education communication from within the family. Similarly, education in society is an integral part of the two pillars Abstrak: Tiga pilar pendidikan yakni keluarga, sekolah dan masyarakat menjadi fondasi membangun peradaban pendidikan masa kini. Tujuan penelitian ini untuk menyadari peran orangtua dan guru sebagai pendamping menanamkan nilai -nilai untuk memajukan martabat dan keluhuran bangsa. Metode yang digunakan peneliti adalah pendekatan kualitatif mempelajari literatur kepustakaan dan juga menggunakan wawancara, sebagai data pendukung. Hasil temuan, berangkat dari beberapa teori yang dikemukakan pada bagian pendahuluan, peneliti menganalisa dalam beberapa media sosial, koran, majalah dan hasil wawancara ditemukan bahwa metode yang relevan dan kreatif dalam mendampingi anak-anak untuk menanamkan nilai-nilai harus sesuai realitas yang dialaminya setiap hari bersama dengan orangtua dalam keluarga, guru di sekolah dan teman-teman masyarakat, sangat membantu peserta didik menemukan jati dirinya. Mendampingi sambil menanamkan nilai, tidak hanya sebuah ungkapan tetapi perbuatan. Karena itu prilaku peserta didik perlu dianalisanya, mengkajinya lebih jauh dan perlu dievaluasi kembali. Dari hasil wawancara, dari tiga pilar ini pendidikan anak dalam keluarga berada di bawah tanggung jawab orang tua. Sementara itu, pendidikan di sekolah dipandang sebagai sarana komunikasi pendidikan lanjutan dari dalam keluarga. Demikian pula pendidikan di masyarakat merupakan bagian integral dari kedua pilar itu